2008
DOI: 10.1007/s12247-008-9030-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of High-shear Granulation using Acoustic Emission: Predicting Granule Properties

Abstract: Sound in the ultrasonic (20 to 1,000 kHz) range emitted during high-shear granulation was recorded and analyzed using multivariate techniques in order to assess the relationship between variations in the physical properties of the obtained granules and the evolution of acoustic emissions taking place during their formation. The acoustic signal analysis was preformed on two different granulators. A four-component model was obtained from the analysis and was capable of predicting the particle size distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Our results share some similarities with research conducted by Whitaker et al (2000) and Gamble et al (2009) who found an increase in the magnitude of the AE during granulation. Papp et al (2008) found a peak in the RMS voltage during the early stages of granulation for the two granulators they studied. Rahmanian et al (2008) found that a faster impeller speed resulted in stronger granules which could be responsible for the higher RMS voltage of the AE.…”
Section: A B Cmentioning
confidence: 88%
See 1 more Smart Citation
“…Our results share some similarities with research conducted by Whitaker et al (2000) and Gamble et al (2009) who found an increase in the magnitude of the AE during granulation. Papp et al (2008) found a peak in the RMS voltage during the early stages of granulation for the two granulators they studied. Rahmanian et al (2008) found that a faster impeller speed resulted in stronger granules which could be responsible for the higher RMS voltage of the AE.…”
Section: A B Cmentioning
confidence: 88%
“…Researchers have used passive acoustics to monitor granulation in HSG (Whitaker et al, 2000;Briens et al, 2007;Daniher et al, 2008;Hansuld et al, 2009;Papp et al, 2008;and Gamble et al, 2009;Hansuld et al, 2011;) and are reviewed in Watson (2010). The majority of all the previous research attempted to identify the granulation end point or granules' properties using complex statistical methods.…”
Section: Passive Acoustic Monitoring Of Granulationmentioning
confidence: 99%
“…fragmentation Pneumatic transport Hou et al 26 Monitoring of flow and related process parameters Albion et al 27 Detection of tablet breakage Albion et al 28 Flow regime detection Albion et al 29 Flow regime detection Granulation Whitaker et al 30 Monitor changes in physical properties, i.e. particle size Briens et al 31 Monitoring Daniher et al 32 End-point detection Papp et al 33 Monitor changes in physical properties Gamble et al 34 End-point detection Hansuld et al 35 End-point detection Hansuld et al 36 Monitoring size and density Hansuld et al 37 Monitoring size Hansuld et al 38 Monitoring changes in process parameters demand for the development of a reliable online or inline monitoring method. The aim of this study was to investigate the potential of passive acoustic emission monitoring of a tumbling V-blender.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic emissions analysis is another direct measurement PAT tool for monitoring the granulation process. The use of acoustic emissions monitoring in the pharmaceutical industry has only picked up pace in the past decade whereas in other fields such as fracture mechanics, non-destructive testing and material science the technique has been used for almost 60 years [11].…”
Section: Introductionmentioning
confidence: 99%